Analisis Usability Testing pada Sistem Informasi Learning Management System (LMS) Universitas Hindu Indonesia Menggunakan Metode System Usability Scale (SUS) - Ariani, Ni Ketut Nopi; Kadek Oky Sanjaya; I Putu Mahendra Adi Wardana (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2025)
Higher education in today's digital era faces the challenge of integrating technology effectively to improve the quality of learning. One of the technologies used is the Learning Management System (LMS), which facilitates interaction between lecturers and students in teaching and learning activities. Universitas Hindu Indonesia (UNHI) has adopted LMS as part of its education digitization strategy. However, the effectiveness of using this LMS has not been thoroughly evaluated, especially in terms of ease of use and user satisfaction. This study aims to assess the usability of the LMS at UNHI using the System Usability Scale (SUS) method. By analyzing data from 97 respondents, the results showed a score of 61, which falls within the 'OK' category and grade 'D'. This indicates that although the LMS provides benefits, there are some areas that require improvement. Key findings show that while ease of use is relatively good, there are significant issues with the mobile interface, notification system, and technical capacity. Recommendations for improvement include enhancing the interface for mobile devices, improving the notification system, and increasing technical capacity to improve the user experience. These findings provide important directions for the development of a more efficient and satisfactory LMS at UNHI.